DEVELOPMENT OF MADURA TRADITIONAL CULINARY AS CULTURAL HERITAGE AND TRADITION - Rachmanto Puji Habibie; Hetti Mulyaningsih; Bangun Sentosa; Bagus Irawan (International Conference on Social and Islamic Studies, 2021)
Madurese traditional cuisine is one of the cultures that has developed and has become a symbol of each region. Culinary may be a special attraction for others. In other words, culinary tourism is a tourist activity that highlights culinary characteristics or delicacy as a tourist attraction. A typical food serves as a sign of an area and can distinguish its existence from other regions. Therefore, the researcher hopes to study the development of Madura's traditional culinary as a cultural heritage and tradition in more depth. Culinary existence has touched all aspects of life and is the foundation of every economy, marking social differences, boundaries, ties and contradictions. The interesting thing about food is the changing discourse on food itself. Changes in discourse that emerged as a result of a shift in viewing food as a practical issue became an aesthetic issue. This study aims to explain concepts and solutions about culinary development on Madura Island as a cultural heritage and tradition with a focus on efforts to improve the culinary existence of Madura in the current era, thus making Madura as an island that is rich in characteristics in the culinary field so that it can compete at the international level. national and international. This effort will ultimately encourage the improvement of the quality of human resources on the island of Madura through Madurese culinary entrepreneurship. This research will be through observation, in-depth interviews and documentation to obtain the desired data. Then this study uses the AGIL scheme from Talcott Parsons as a theoretical basis. Using primary and secondary data sources to support the completeness and validity of the data.